Osteometric Study of Metapodial Bones and Phalanges as Indicators of the Behavioural Ecology of Modern Reindeer (Rangifer tarandus) and Implications for Reconstruction of Paleo Mobility - Galán López, Ana; Costamagno, Sandrine; Burke, Ariane (Open Quaternary, 2022)
Paleolithic reindeer (Rangifer tarandus) played an important role for human populations in western and central Europe during much of the Paleolithic period. In southwestern France and in particular during the Magdalenian, reindeer frequently figures among the privileged prey of hunter-gatherer groups. However, and despite numerous attempts to reconstruct the migratory behavior of Paleolithic reindeer, there is no agreement on the degree of mobility of this prey. Modern ethological data indicate that reindeer herds adopt different mobility strategies depending on the type of habitat and the topography of the environment. Thus, our project (Emorph) aims to explore morphometric criteria (through metapodial bones and phalanges) in combination with cutting-edge methodologies like Machine Learning to identify the extent of reindeer migrations. Based initially on the study of modern caribou populations with distinct migratory behaviors, the results obtained could be applied to several Magdalenian assemblages from southwestern France in the future, with the goal of reconstructing the mobility of these tardiglacial reindeer.